Value of Preoperative Imaging Results in Predicting Cochlear Nerve Function in Children Diagnosed With Cochlear Nerve Aplasia Based on Imaging Results - Chao, Xiuhua; Wang, Ruijie; Luo, Jianfen; Wang, Haibo; Fan, Zhaomin; Xu, Lei (Frontiers in Neuroscience, 2022)
This study aimed to assess the function of the cochlear nerve using electrically evoked compound action potentials (ECAPs) for children with cochlear implants who were diagnosed with cochlear nerve aplasia and to analyze the correlation between preimplantation imaging results and ECAP responses. Thirty-five children diagnosed with cochlear nerve aplasia based on magnetic resonance imaging (MRI) were included. Preimplantation MRI and high-resolution computed tomography (HRCT) images were reconstructed, and the width of the bone cochlear nerve canal (BCNC), the diameter of the vestibulocochlear nerve (VCN), and the diameter of the facial nerve (FN) were measured. ECAP input/output (I/O) functions were measured at three electrode locations along the electrode array for each participant. The relationship between ECAP responses (including ECAP threshold, ECAP maximum amplitude, and slope of ECAP I/O function) and sizes of the BCNC and VCN was analyzed using Pearson's correlation coefficients. Our analysis revealed that ECAP responses varied greatly among individual participants. Overall, ECAP thresholds gradually increased, while maximum amplitudes and ECAP I/O function slopes gradually decreased, as the electrode location moved from the basal to the apical direction in the cochlea. ECAP responses exhibited no significant correlations with BCNC width or VCN diameter. The ratio of the VCN to FN diameters was significantly correlated with the slope of the ECAP I/O function and the maximum amplitude. BCNC width could not predict the function of the cochlear nerve. Compared with the absolute size of the VCN, the size of the VCN relative to the FN may represent an indicator for predicting the functional status of the cochlear nerve in children diagnosed with cochlear nerve aplasia based on imaging results.